Whistleblowing and Tri Hita Karana to Prevent Village Fund Fraud in Bali - Komang Adi Kurniawan Saputra; I Ketut Puja Wirya Sanjaya (Yayasan Rumah Peneleh, 2019)
This study aims to examine the whistleblowing and Tri Hita Karana variables on fraud prevention in managing village funds. This study used a survey method with a questionnaire, while the method of determining the number of samples was the Slovin formula, which produced 88 villages as samples that received village funds in the Province of Bali. Data collection was done using personally administered questionnaires (personal questionnaires), which means that researchers can relate directly to the respondent and provide explanations as needed about the questionnaire and can be collected immediately after the respondent has answered them. Data analysis was conducted by using ordinary least square model multiple linear regression. The results of this study indicates that Tri Hita Karana culture significantly influences fraud prevention in managing village funds, while the whistleblowing variable does not show a significant effect on the prevention of fraud in village fund management. In village government and village fund management, mutual trust and mutual respect are regarded better compared to mutual accusation, meaning that the village government in Bali believes in national law and customary law in overcoming fraudulent perpetrators.